(untitled) (Innovaciones Educativas, 2025)
This document has as its general objective to analyze the results obtained from a form applied to principals of educational institutions in circuit 04 of the San José Oeste Regional Education Office (DRESJO, for its acronym in Spanish), regarding quality management that guarantees an accessible, equitable, and sustainable education as a right. The study was carried out from a quantitative approach and a descriptive method, with a non-probabilistic convenience sample, without exclusion criteria, considering the availability and accessibility of the 37 participants through digital means; furthermore, the information was analyzed with statistical procedures. As a main result, a trend was found towards an education with areas for improvement and many barriers to legitimizing this right. Finally, the main conclusion refers to the emergence of education as a right, with challenges and priorities regarding accessibility, equity, and sustainability that are mainly related to the scarcity of resources, deficiencies in the specialized training of the teaching staff, and the lack of adequate infrastructure.